Priority nutrients to address malnutrition and diet-related diseases in Australia and New Zealand - Starck, Carlene S.; Cassettari, Tim; Beckett, Emma; Marshall, Skye; Fayet-Moore, Flavia (Frontiers in Nutrition, 2024)
Background: The double burden of malnutrition and diet-related disease has been attributed to diets high in ultra-processed and discretionary foods, with increased sugars, saturated fats, and sodium, and insufficient dietary fibre. There is a limited understanding of the role of other macronutrients and micronutrients. Objective: Determine the highest priority nutrients to address both malnutrition and dietrelated disease in Australia and New Zealand, for each demographic group and the total population. Methods: A novel four-step methodological approach was undertaken to identify: 1. Demographic (age-sex) groups; 2. Health priorities; 3. Potential nutrients based on inadequacy, increased requirements, and health priority association; and 4. Priority nutrients. Nutrient intake data was obtained from the most recent Australian and New Zealand nutrition surveys. Health priorities were based on national statistical data and expert consultation. High-level scientific literature (systematic reviews) was scoped for associations with health priorities and the suitability of recommended intakes. A quantitative scoring matrix was developed and used to determine the highest priority nutrients, with scoring over three domains: extent of inadequacy; consensus for increased requirements; and degree of association with health priorities. Results: Nutritional inadequacies were common, with 22 of 31 essential nutrients consumed below recommended levels. Nine priority nutrients were identified across the demographic groups, with each demographic group characterised by a specific subset of these. Six nutrients were highest priority within the total population: vitamin D, calcium, omega-3 fatty acids, magnesium, folate, dietary fibre. Conclusions: The extent of nutritional inadequacies in Australia and New Zealand is high, both within each demographic group and the entire population, relative to both recommended intakes and key health outcomes. The methodology can be applied to other countries and globally. Findings make a significant contribution to understanding the nutrients to prioritise in future-proofing the health of the Australian and New Zealand populations. Guidelines and policies can target priority nutrients to address the malnutrition and diet-related disease double burden.